Computer-mediated leadership: Deficits, hypercharisma, and the hidden power of social identity - Oliver Fischer; Antony S. R. Manstead (Zeitschrift für Personalforschung (ZfP), 2004)
This paper sketches a theory of computer-mediated leadership, drawing on research on computer-mediated communication (CMC) and leadership. The forecast it makes for computer-mediated forms of leadership is mixed. Leadership interactions that focus on the personal and dyadic level are predicted to be deficient under conditions of CMC as compared with face-to-face interaction. Two notable exceptions are identified. If message or task equivocality is low, CMC can be more efficient than face-toface interaction. The second exception concerns attributions of charisma: For leaders who present themselves skilfully and strategically in CMC, followers' impressions are hypothesised to become accentuated or 'hypercharismatic'. The above effects are all hypothesised to occur under conditions of high salience of the personal identities of both leader and follower. If, however, the leader and follower belong to the same salient and positively evaluated group, the effects of CMC are hypothesised to be positive. These effects are a direct result of integrating the SIDE-theory of computermediated communication and Hogg's social identity theory of leadership.
Keywords: 650; Computer-mediated Leadership; Computer-mediated Communication (CMC); E-leadership; Social Identity Theory; Hypercharisma